Knowledge-based support for object-oriented software design and synthesis: A category theoretic approach - Zheng, Y.; Xue, J.; Hu, Q. (Journal of Digital Information Management, 2007)
To reuse previous knowledge of objectoriented design and adapt them to solve new problems, the collaboration relationships and the responsibility distribution among software objects need to be thoroughly understood and precisely formulated. The paper proposes a knowledge-based approach that employs category theoretic models to formalize and mechanize objectoriented software design and synthesis by focusing concern on reasoning about the interdependency relationships at different levels of abstraction and granularity. The major benefit of our approach is twofold: First, it provides an explicit semantics for formal object-oriented specifications, and therefore enables a high-level of reusability and dynamic adaptability. Second, it utilizes the ability of categorical computations to support automated software composition and refinement. A prototype tool that demonstrates the feasibility and effectiveness of our approach is also presented.
Keywords: Automated software; Object oriented design; Software metrics; Software quality